Hubungan Karakteristik Wanita Usia Subur (WUS) dengan Penyakit Kanker Serviks - Luh Ayu Purnami; Kadek Ayu Suarmini; Putu Indah Sintya Dewi; Ni Ketut Wulandari; Mochamad Heri (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to determine the relationship between the quality of women of childbearing age (WUS) based on age, education, occupation, parity, and history of contraceptive use with cervical cancer growth. This research method is analytically observational with a case-control study design. The results of univariate analysis of 118 respondents aged>35 years were 71 people (60.2%), high school education level was 47 people (39.8%), work as housewives (IRT) was 35 people (29.7% ), respondents with parity as many as 65 people (55.1%) and the use of non-hormonal contraception as many as 56 people (47.5%). The results of this study found that there was a significant relationship between age, occupation, and parity (Î±=<0.05). In contrast, employment and history of contraceptive use did not show any association with cervical cancer (Î±>0.05). The results of data analysis with the chi-square test got a value of 0.025 or p <Î± (0.05). In conclusion, there is a significant relationship between age, occupation, and parity with cervical cancer. Keywords: Cervical Cancer, Women of Childbearing Age